2023
DOI: 10.1186/s40643-023-00660-5
|View full text |Cite
|
Sign up to set email alerts
|

Different photosynthetic responses of haploid and diploid Emiliania huxleyi (Prymnesiophyceae) to high light and ultraviolet radiation

Abstract: Solar radiation varies quantitatively and qualitatively while penetrating through the seawater column and thus is one of the most important environmental factors shaping the vertical distribution pattern of phytoplankton. The haploid and diploid life-cycle phases of coccolithophores might have different vertical distribution preferences. Therefore, the two phases respond differently to high solar photosynthetically active radiation (PAR, 400–700 nm) and ultraviolet radiation (UVR, 280–400 nm). To test this, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…8; Supplementary Text; Dataset S4). The presence of flagella and a likely more mixotrophic nutrition in the haploid are in contrast with more abundant chlorophyll a (37,38) and the up-regulation of photosynthesis-related genes in the diploid. The low abundance of DMSP in the haploid (29) is possibly due to the up-regulation of DMSP catabolic enzymes in both demethylation and cleavage pathways, including two key DMSP lyases, DddD and Alma.…”
Section: Discussionmentioning
confidence: 97%
“…8; Supplementary Text; Dataset S4). The presence of flagella and a likely more mixotrophic nutrition in the haploid are in contrast with more abundant chlorophyll a (37,38) and the up-regulation of photosynthesis-related genes in the diploid. The low abundance of DMSP in the haploid (29) is possibly due to the up-regulation of DMSP catabolic enzymes in both demethylation and cleavage pathways, including two key DMSP lyases, DddD and Alma.…”
Section: Discussionmentioning
confidence: 97%
“…huxleyi 58,74 . However, in our experiments, cultures subjected to UV did not exhibit a comparable effect (Figure S5).…”
Section: External Application Of Vitamin D Impacts Algal Traits Simil...mentioning
confidence: 99%
“…For example, the non-calcified strain exhibited photoinhibition under a moderate level of irradiance of above 400~500 µmol m −2 s −1 [24]. The photosynthesis of the non-calcified haploid strain RCC 1217 exhibited greater sensitivity to high visible light levels compared to the calcified strain PML B92/11, but demonstrated resistance to ultraviolet radiation (UVR)-induced inhibition, demonstrating a capacity to adapt to a specific ecological niche [33]. Previous studies have indicated that cellular organic contents between the two morphotypes may differ, but the results have been inconsistent across experiments.…”
Section: Introductionmentioning
confidence: 99%